Pengaruh Komponen Kecerdasan Emosional pada Pemahaman Akuntansi - Sukma Mutiara Pramita Sari, Made; Wirama, Dewa Gede (E-Jurnal Akuntansi, 2019)
Accounting education in college is intended to educate students to work a s professional accountant s with knowledge in accounting. Understanding of accounting is the process to understand accounting both as knowledge and as a process or practice. Understanding of accounting can be influenced by emotional intelligence of each individual . The purpose of this study is to determine the effect of the components of emotional intelligence on accounting understanding. This research was conducted at the Faculty of Economics and Business, Udayana University. The number of samples was 111 students, using non probability sampling methods. Data collection is conducted through a questionnaire. The data analysis technique used is multiple linear regression analysis. Based on the results of the analysis it was found that the component s of emotional intelligence had positive effects on accounting understanding. The higher self-recognition, self-control, motivation, empathy and social skills, the higher the understanding of accounting. Keywords: Accounting, emotional intelligence, accounting students.